2021
DOI: 10.1002/ppul.25549
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant and antioxidant balance in patients with COVID‐19

Abstract: Background: A crucial balance exists between oxidant and antioxidant mechanisms in the functional immune system. We aimed to evaluate the contributions of balance between these systems to coronavirus disease 2019 (COVID-19), a devastating pandemic caused by viral infection.Method: We analyzed serum oxidant and antioxidant stress parameters according to the clinical and demographic characteristics of children and adults with COVID-19 and compared them against the values of healthy controls. Serum native thiol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
2
27
2
Order By: Relevance
“…These results further suggest that in addition to decreased p53 abundance, the functionality of the remaining p53 could be impaired in cells infected by SARS-coronaviruses. Impairment of p53 functions is of particular concern because during severe COVID-19 illness, the patients develop a pro-oxidant state that is also correlated with sustained oxidative DNA damage (discussed below) [ 56 , 57 ], which could increase the probability of a blunted response to DNA damage. Notably, an increase of p53 degradation and the resultant impairment of its normal cell functions are common characteristics of other viruses such as Epstein-Barr virus and human herpes simplex virus-1 [ 52 ].…”
Section: Potential Direct Mechanisms Of Coronaviruses To Induced Dna Damagementioning
confidence: 99%
See 2 more Smart Citations
“…These results further suggest that in addition to decreased p53 abundance, the functionality of the remaining p53 could be impaired in cells infected by SARS-coronaviruses. Impairment of p53 functions is of particular concern because during severe COVID-19 illness, the patients develop a pro-oxidant state that is also correlated with sustained oxidative DNA damage (discussed below) [ 56 , 57 ], which could increase the probability of a blunted response to DNA damage. Notably, an increase of p53 degradation and the resultant impairment of its normal cell functions are common characteristics of other viruses such as Epstein-Barr virus and human herpes simplex virus-1 [ 52 ].…”
Section: Potential Direct Mechanisms Of Coronaviruses To Induced Dna Damagementioning
confidence: 99%
“…Moreover, chronic inflammation is associated with the production of reactive oxygen species that can promote the development of some types of cancer, insulin resistance and vascular lesions [ [77] , [78] , [79] ]. In COVID-19 patients, serum levels of glutathione and total thiol are decreased, while levels of superoxide dismutase, catalase, malondialdehyde (a marker of oxidative stress and lipoperoxidation) and the total oxidant status are increased [ 57 , [80] , [81] , [82] ]. Oxidative stress levels correlated with blood oxygen saturation levels, disease severity, prognosis, and with the virus variant that was causing the infection [ 57 , 80 , 82 , 83 ].…”
Section: Potential Indirect Mechanisms Of Sars-cov-2 Induced Dna Damage: Aberrant Inflammation Immune Response and Oxidative Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress may be a key player in COVID-19 pathogenesis due to its significant role in response to infections [ 7 ]. Several studies have reported some viruses’ ability to disrupt redox balance of a cell to ensure survival [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, Aykac et al found that total antioxidant and total oxidant status were similar for both mild, moderate, and severe groups of hospitalized pediatric and adult patients [ 88 ]. Although both studies included a similar number of patients, 96 [ 87 ] and 86 [ 88 ], respectively, it is difficult to compare both studies as they have used different World Health Organization (WHO) interim guidelines for categorization of disease severity, the first from March 2020 [ 87 ] and the second from May 2020 [ 88 ]. Furthermore, there was insufficient data on inclusion and exclusion criteria for patients in the Aykac et al paper [ 88 ].…”
Section: Oxidative Stress and Covid-19 Severitymentioning
confidence: 99%